Socket Preservation Using Autogenous Tooth Graft: An in vivo study - Mostafa kamal Aql ; Amr Aly El-Swify ; Abdelbadia Abdullah Abdelmabood ; Mohamed Hassan Eid (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Tooth loss is still considered an epidemic condition affecting populations in different areas of the world. The aim of the present study was to evaluate efficiency of using autogenous tooth graft for socket preservation clinically and radiographically. Patients and methods: Seventeen patients with two single rooted teeth indicated for extraction in the same dental arch. The two extraction sockets were allocated to Group A (test group): Socket grafted with autogenous tooth graft; and Group B (control group): Socket left ungrafted (control). Results: There was no statistically significant difference between the two groups as regard age or sex. Concerning Buccal bone loss, There was statistically significant difference between the two groups at day 90 (P=0.045) and Change (P